Gambaran Pendidikan Karakter Disiplin di Era Digital Pada Siswa Kelas V di SDN 02 Laladon Bogor - Nabilah Farhah; Fitira Rosmi; Dace (TADRUSUUN: JURNAL PENDIDIKAN DASAR, 2024)
This study aims to describe the character education of discipline in grade V students of SDN 02 Laladon Bogor in the digital era. The digital era has a significant impact on the development of character education, especially discipline. This study uses a qualitative method with data collection techniques through observation, interviews, and documentation studies. The results of the study indicate that character education of discipline in grade V students of SDN 02 Laladon Bogor faces challenges and opportunities in the digital era. Factors such as the use of technology, parenting patterns, and school environment influence the formation of students' disciplined character. These findings provide insight into the efforts that need to be made in improving character education of discipline in the digital era, including the development of relevant learning methods and the active role of parents in supporting character education at home. This study is expected to contribute to increasing understanding and awareness of the importance of character education of discipline in changing times. The practical implications of this study can be used as a guideline for educators, parents, and related parties in designing effective strategies to develop discipline in grade V students in the digital era.